Arterial hypertension in kidney transplant recipients: pathophysiology, diagnostics, treatment - M. Sh. Khubutiya; F. M. Musaeva; T. A. Kanunova; O. N. Rzhevskaya; A. G. Balkarov; Kh. G. Alidzhanova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2024)
Relevance: Arterial hypertension (HTN) in kidney transplant recipients is a major risk factor for cardiovascular diseases, graft rejection and premature death. In the post-transplant period in 80% of cases persistent or refractory arterial hypertension develops which is difficult to correct with conventional drug therapy. Treatment difficulties include the ineffectiveness of many first-line drugs and the fact that the most common immunosuppressive drugs (cyclosporine, tacrolimus and methylprednisolone) contribute to the development of hypertension. This type of hypertension represents a significant problem in clinical practice due to the complexity of treatment and high mortality. The need to study the treatment of post-transplant hypertension is due not only to its clinical significance, but also to the potential opportunity to improve treatment results and life expectancy of kidney transplant recipients.Objective: to study the genesis, risk factors, pathophysiology, diagnosis and treatment of posttransplant hypertension.Materials and methods: 37 literary sources were analyzed.Conclusions: High blood pressure exposes the recipient of a kidney transplant to the risk of CVD and mortality as well as increased systemic hypertension which can be a cause and a consequence of renal pathology. Hypertension is a modifiable risk factor contributing to the progression of renal failure. There is no any single treatment algorithm. It is often necessary to use several antihypertensive drugs to achieve the target blood pressure.